First Latin American Forum in Transplant Bioethics: The Aguascalientes Document - Baquero, Ashley; Alberú, Josefina; Abbud-Filho, Mario (Brazilian Journal of Transplantation, 2010)
The questionings of a bioethical order, related to organ transplants, posed in the second half of the twentieth century, have motivated intense debates and have constituted an authentic challenge for the scientific, legal, moral and religious ambits during all these years. The question would then be asked as to why – half a century later – the debate regarding the bioethics of transplants is still open? The first Forum on Transplant Bioethics was conceived in the core of the Latin American and Caribbean Transplant Society The Forum originated due to the necessity of creating a space that would permit the analysis of the existing problems in the region. The necessity for reflection was detected, solutions had to be looked for in some cases; in others, we would look to establishing a consensual positioning; in other aspects we would limit ourselves to proposing solutions. The transplant community of Latin America could not remain detached from such a series of problems; they considered it a duty never to be given up. The Document of Aguascalientes reaffirms its identity with the highest values defining the practice of medicine; it reaffirms its commitment with dignity, its respect for life and the never-to-be given up duty of helping those who suffer. Although the Document of Aguascalientes admits that each country and each transplant center have the prerogative of defining their own practices, it does pretend to serve as an instrument of expression on behalf of the groups with transplanting activity in Latin America and the Caribbean, and its aim is to influence the realization of the transplant activities in an atmosphere of justice and equity.